THEORETICAL PERSPECTIVES AND PRACTICES OF MOBILE-ASSISTED LANGUAGE LEARNING AND MIND MAPPING IN THE TEACHING OF WRITING IN ESL CLASSROOMS - Abu, Abdul Ghani; Karim, Rafidah Abd (Universitas PGRI Adi Buana Surabaya, 2017)
Mobile assisted language learning (MALL) is a highly popularmultidisciplinary study field which increasingly attracts the attention ofscholars around the world. Moreover, it has attracted the scholars whohave realized the potential to apply mobile technologies to enhancelearning. This paper explores the perspectives and practices of mobileassistedlanguage learning and mind mapping and their practices inteaching of writing in the ESL classrooms. Few aspects are covered likedefining MALL, theoretical perspectives drawn from MALL, relatingthese to the practice of MALL and mind mapping in writing, pedagogicalapproaches used in MALL and issues faced in the ESL writingclassrooms. Thus, it is showed that MALL can be incorporated intowriting by using it with several writing approaches and techniques whichcounterparts the pedagogical advantages in mobile language learningcontexts. The paper concludes with a brief discussion of the reviewedstudies and it implicates that mobile learning and mind mapping has goodprospects for teaching writing to ESL students.